IN VITRO REGENERATION OF MULTIPLE SHOOTS FROM THE NODAL EXPLANTS OF DRYMARIA CORDATA (L.) WILLD. EX. ROEM. AND SCHULT - D. H. TEJAVATHI,; M. N. INDIRA, (The Bioscan, 2011)
Drymaria cordata commonly known as West Indian chick weed is widely exploited for its medicinal properties. An efficient protocol for in vitro multiplication of Drymaria cordata using nodal explants is developed. Nodal cultures were raised on Murashige and Skoog’s medium (MS) supplemented with auxins and cytokinins either alone or in combination with various auxins. Maximum number of shoots (19.51 ± 0.18) with high frequency of shooting response (76.6%) was obtained in nodal cultures on MS medium fortified with BAP (4.44μM) alone. The in vitro regenerated shoots were rooted in MS + IBA (0.49 μM). The plantlets obtained were successfully hardened and established in soil. Nearly 90% of survival was recorded.